Hospitality and leisure between religious maxims and modern facilities - Shuriye, Abdi Omar; Haji Che Daud, Mohd Radzi (MCSER Publishing, 2014)
The word host means stranger or enemy in it is Latin origin and hospitem stands for guest in Latin. The English language therefore derives various words from this origin including hospital, host, hostel, hotel and hospitality. In our contemporary world there has been an increasing focus on Islamic services related to hospitality; and in fact, halal revolution has created awareness among Muslims in leisure and hospitality services and consumption. In order to cater for this demand hotels are becoming innovative in products, food, and services. Nonetheless, to synchronize religious maxims and modern facilities has never been an easy task for this industry. This paper is part of a major research on the concept of Halalan Tayibah as stipulated in the Qur’an. The aim of the research in its complete sense is to examine and illustrate several features and the characteristics of hospitality services offered in Islamic compliant hotels in Kuala Lumpur.